House Prices, Local Demand, and Retail Prices - Johannes Ströbel; Joseph Vavra (Center for Economic Studies and ifo Institute (CESifo), 2015)
We use detailed micro data to document a causal response of local retail price to changes in house prices, with elasticities of 15%-20% across housing booms and busts. Notably, these price responses are largest in zip codes with many homeowners, and non-existent in zip codes with mostly renters. We provide evidence that these retail price responses are driven by changes in markups rather than by changes in local costs. We then argue that markups rise with house prices, particularly in high homeownership locations, because greater housing wealth reduces homeowners' demand elasticity, and firms raise markups in response. Consistent with this explanation, shopping data confirms that house price changes have opposite effects on the price sensitivity of homeowners and renters. Our evidence has implications for monetary, labor, and urban economics, and suggests a new source of markup variation in business cycle models.
Keywords: E31; E44; E52; L16; R21; R22; 330